Injury to the Extrasellar Portion of the Internal Carotid Artery during Endoscopic Transsphenoidal Surgery: A Case Report - Teramoto, Shinichiro; Tahara, Shigeyuki; Murai, Yasuo; Sato, Shun; Hattori, Yujiro; Kondo, Akihide; Morita, Akio (Frontiers in Surgery, 2022)
Background Injury to the internal carotid artery (ICA) during endoscopic transsphenoidal surgery (ETSS) is a serious complication with a risk of mortality. ICA injury during ETSS usually occurs during intrasellar manipulations and rarely occurs in the extrasellar portion. Several hemostatic procedures have been proposed for ICA injury in the intrasellar portion, whereas hemostatic methods for ICA injury in the extrasellar portion, where the ICA is surrounded by bone structures, are less well known. Case Presentation A 65-year-old man with an incidental pituitary tumor underwent ETSS. The petrous portion of the left ICA was injured during resection of the sphenoid septum connected with left carotid prominence using a cutting forceps. Bleeding was too heavy for simple hemostatic techniques. Hemostasis using a crushed muscle patch was tried unsuccessfully during controlling of the bleeding. Eventually, the injured site of the ICA was covered with cotton patties followed by closing with a vascularized pedicled nasoseptal flap. Cerebral angiography immediately after surgery showed no extravasation from the injured site of the left ICA petrous portion. However, a carotid-cavernous sinus fistula originating from the injured ICA site was detected 7 days after surgery, so the vascular reconstructive surgery combined with left ICA occlusion was performed. The overall postoperative course was uneventful. Conclusion We believe that emergency application of the cottonoids may be effective for hemostasis against ICA injury in the extrasellar portion during ETSS, but further vascular reconstruction combined with ICA occlusion on the injured side and removal of the cottonoids would be required.